2012
DOI: 10.1002/ppap.201100157
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Atmospheric Pressure Plasma‐Enhanced Chemical Vapor Deposition of Thin Films from Methyldisiloxane Precursors

Abstract: This work describes the plasma‐enhanced chemical vapor deposition of thin films at atmospheric pressure using dielectric barrier discharges fed with argon, oxygen and different methyldisiloxanes, i.e., hexamethyldisiloxane, pentamethyldisiloxane, and 1,1,3,3‐tetramethyldisiloxane. The influence of the methyldisiloxane chemical structure and of the oxygen/methyldisiloxane feed ratio is investigated in order to provide insights into the organosilicon plasma chemistry at atmospheric pressure. As expected the FT‐I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…PVD is commonly used to form a thin layer of carbide or nitride on steel in applications such as cutting tools, but it can also allow for pulverisation of metal oxides over wood. Sonnenfeld et al (2001) and Fanelli et al (2012) also observed dissociation of the HMDSO through scission of the Si-O and Si-CH 3 bonds. CVD is a chemical process used to produce high-purity, high-performance solid materials.…”
Section: Common Deposition Techniquesmentioning
confidence: 94%
“…PVD is commonly used to form a thin layer of carbide or nitride on steel in applications such as cutting tools, but it can also allow for pulverisation of metal oxides over wood. Sonnenfeld et al (2001) and Fanelli et al (2012) also observed dissociation of the HMDSO through scission of the Si-O and Si-CH 3 bonds. CVD is a chemical process used to produce high-purity, high-performance solid materials.…”
Section: Common Deposition Techniquesmentioning
confidence: 94%
“…[26][27][28] More general plasma chemical pathways of thin film deposition from organosilicon precursors in atmospheric pressure DBDs were investigated in. [29][30][31] From the application point of view it is necessary to know how and why the barrier film quality depends on the reactor throughput. In the case of thin film deposition on a moving web the throughput is expressed by the dynamic deposition rate (DDR) value, defined as the product of film thickness and web transport speed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, detailed structural insight into these thin films would allow plasma polymerization processes to be better understood, and hence optimized in a rationalized manner. A general deposition mechanism for the HMDSO precursor in atmospheric pressure plasma polymerization was very recently proposed by Fanelli et al,6–8 based on the knowledge of species detected in the exhaust gas and the chemical composition of the plasma‐polymer deposits. This mechanism mainly considers radical‐driven recombination of methyl, trimethylsilyl, trimethylsiloxy, and pentamethyldisiloxy radicals produced under HMDSO dissociation via the cleavage of SiC or SiO bonds.…”
Section: Introductionmentioning
confidence: 99%